Geography study guide grade 12 - Davidson, Gail; Grey, Julia (Mind the gap study guides for grade 12, 2012)
These study guides are another innovative and committed attempt by the Department of Basic Education to improve the academic performance of Grade 12 candidates in the National Senior Certificate (NSC) examination. The Mind the Gap study guide series is produced in both English and Afrikaans to assist those learners that have been underperforming due to a lack of exposure to the content requirements of the curriculum. The series aims to mind-the-gap between failing and passing, by bridging-the-gap in learners’ understanding of commonly tested concepts so candidates can pass. Each of the Mind the Gap study guides provides explanations of key terminology, simple explanations and examples of the types of questions that learners can expect to be asked in an exam. Model answers are included to assist learners in building their understanding.